Strategi pengelolaan sampah melalui pendekatan SWOT: studi kasus Pondok Pesantren Qur’an Al-Hikmah Bogor - Dino Rimantho; Nur Yulianti Hidayah; Agung Saputra; Averina Chandra; Ananda Nurul Rizkiya; Ghina Nazhifah; Defi Milenia Putri Wesha; Pipit Fitriyani (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Management of waste is a serious problem in every nation. The volume of waste, the limited location for disposal, and the threat of reducing environmental and health risks are some of the factors that encourage the occurrence of quite complex problems in waste management. Thus the waste management strategy in the Qur'an Al-Hikmah Islamic boarding school is the goal of this paper. This study uses the SWOT method as a tool to determine waste management strategies. In addition to that, a questionnaire was also utilized throughout the course of this research. This questionnaire was distributed to five respondents who understand the problem of waste at Pondok Pesantren Qur'an Al-Hikmah Bogor.. The results of the analysis provide information about internal factors and external factors. In addition, the topic presented in this article offers the outcomes of a SWOT analysis pertaining to waste management. These outcomes are located in quadrant I (Strength-Opportunity strategy) and total around 7.223 points. This demonstrates that Islamic boarding schools have a number of really good capabilities that can be used to identify the options that they have available to them. The results can be replicated in other educational institutions as a strategy for sustainable environmental management.